2017
DOI: 10.1016/j.dadm.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of criteria for subjective cognitive decline and preclinical Alzheimer's disease in a memory clinic sample

Abstract: IntroductionSubjective cognitive decline (SCD) and biomarker-based “at-risk” concepts such as “preclinical” Alzheimer's disease (AD) have been developed to predict AD dementia before objective cognitive impairment is detectable. We longitudinally evaluated cognitive outcome when using these classifications.MethodsMemory clinic patients (n = 235) were classified as SCD (n = 122): subtle cognitive decline (n = 36) and mild cognitive impairment (n = 77) and subsequently subclassified into SCDplus and National Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 54 publications
4
31
0
Order By: Relevance
“…SCD was assessed using the Memory failures in everyday life following severe head injury [28] and the Subjective Cognitive Decline Questionnaire (SCD-Q) [29]. Although SCD has been recently included in the preclinical stage of AD [30, 31], its identification in the healthy aging population is essential [32] due to their association with a higher risk of AD [33, 34]. …”
Section: Methodsmentioning
confidence: 99%
“…SCD was assessed using the Memory failures in everyday life following severe head injury [28] and the Subjective Cognitive Decline Questionnaire (SCD-Q) [29]. Although SCD has been recently included in the preclinical stage of AD [30, 31], its identification in the healthy aging population is essential [32] due to their association with a higher risk of AD [33, 34]. …”
Section: Methodsmentioning
confidence: 99%
“…Persons with SCD complain about their memory but present scores within the normal range on standardized neuropsychological tests. It has been shown that a significant proportion of those individuals will later develop MCI and AD dementia, particularly if they display biomarker evidence of AD ( Eckerström et al, 2017 ) or express worry about this perceived change in cognitive ability in addition to their memory complaints ( Jessen, Amariglio, et al, 2014 ; Reisberg, Shulman, Torossian, Leng, & Zhu, 2010 ). Hence, SCD might be considered as an interesting construct to study the first clinico-pathological manifestations of AD ( Dubois et al, 2016 ; Sperling et al, 2011 ).…”
mentioning
confidence: 99%
“…Eckerström et al . followed up 122 SCD subjects for a mean time of 48 months and found a very poor accuracy of SCD‐plus criteria as predictors of AD. More recently, a cross‐sectional description of participant characteristics in an ongoing prospective cohort study on SCD showed that age ≥60 and ApoE ε4 were associated with positivity of cerebrospinal fluid biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, SCD‐plus represents an open set of criteria reflecting current knowledge, which allows for addition and subtraction of items as research progresses. Only one longitudinal study which assessed SCD‐plus criteria in predicting the risk of conversion to AD is known which found a very poor accuracy of SCD‐plus criteria. However, that study considered only a 24‐month follow‐up time.…”
Section: Introductionmentioning
confidence: 99%